Exploring consumer justification of overconsumption in live streaming e-commerce in China : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Marketing at Massey University, Albany, New Zealand - Chang, Yuan (Massey University, 2025)
The aim of this research is to explores how Chinese consumers perceive sustainable consumption and how these perceptions are shaped and enacted within livestream e-commerce environments. While sustainable consumption has gained increasing scholarly attention, most existing research adopts quantitative approaches and focuses on Western contexts, leaving a gap in understanding how sustainability is subjectively constructed and behaviorally rationalized in China’s rapidly evolving digital marketplaces. Drawing on 18 semi-structured interviews and guided by a constructivist epistemology, this study employs thematic analysis to uncover the layered understandings, tensions, and justifications surrounding sustainability in the context of livestream shopping. The findings from this research reveal that consumers often equate sustainability with product durability, frugality, and personal responsibility, but also experience internal conflicts when navigating entertainment-driven shopping platforms. The study highlights how platform features—such as interactivity, persuasive streamer tactics, and ease of returns—both complicate and facilitate sustainable decision-making. Furthermore, consumers adopt various rationalization strategies, including neutralization techniques, to justify overconsumption. This research contributes to sustainability literature by contextualizing consumer behavior in emerging digital economies and expanding the application of ethical consumption theories to livestream retail. Practical implications are offered for platform designers, marketers, and policy makers seeking to promote sustainability in e-commerce.
Keywords: 350601 Consumer behaviour